Increasing Operational Effectiveness of the Enterprise by Using the Methods of Lean Manufacturing and Six Sigma - Alexey Georgievich KORYAKOV; Oleg Igorevich ZHEMERIKIN; Martinas PRAZAUSKAS (Communications of International Proceedings, 2020)
As a rule, the problem of improving the operational effectiveness of the enterprise is in the responsibility of its key managers. The concepts of Lean manufacturing and Six Sigma (Lean Six Sigma) transpose these tasks on all the processes and areas of the creation of the product’s value. The positive experience of Honeywell demonstrates how the operational effectiveness of the enterprise can be increased by incorporating the methods of Lean Six Sigma into the production system. This article discusses the main elements of the Honeywell operating system that may influence its operation efficiency. The specific examples of the use of Lean and Six Sigma methods at a Russian enterprise are given. The method of Tier meetings, which enables to increase the operational effectiveness by means of timely identification of production problems, is described. The conclusion highlights the possibility of spreading this experience to other Russian enterprises.
Keywords: lean manufacturing; six sigma; operational effectiveness; Tier meetings; Honeywell operating system (HOS).